2009
DOI: 10.1055/s-0029-1210480
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Plasma Canine C-Peptide by Radioimmunoassay

Abstract: A sensitive radioimmunoassay (RIA) for canine C-peptide (CCP) was established using synthetic CCP, a specific antiserum, and rabbit anti-guinea pig serum. Radioiodination was performed according to a modified chloramine-T method. Tracer preparations were used for long as 6 weeks after iodination. The standard curve ranges from 0.028 to 3.0 nmol/l. The intra-assay coefficient of variation (CV) was 3-5% and the inter-assay CV was 6-9% in the optimal range between 0.3 and 0.8 nmol/l. The average recovery of CCP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There are marked species differences in the C‐peptide molecule, so specific immunoassays are needed (Peterson and others 1972). Several radioimmunoassays have been developed and validated for measuring C‐peptide in dogs, using C‐peptide isolated from dog pancreas (Polonsky and others 1983) and synthetic canine C‐peptide (Kawanishi and others 1980, Besch and others 1985); however, no commercial C‐peptide assay for use in dogs was available until recently. This assay (Linco Research) has been shown to be effective for measuring pancreatic β‐cell function in diabetic dogs and in dogs with endogenous insulin hypersecretion (Boyd and others 2004).…”
mentioning
confidence: 99%
“…There are marked species differences in the C‐peptide molecule, so specific immunoassays are needed (Peterson and others 1972). Several radioimmunoassays have been developed and validated for measuring C‐peptide in dogs, using C‐peptide isolated from dog pancreas (Polonsky and others 1983) and synthetic canine C‐peptide (Kawanishi and others 1980, Besch and others 1985); however, no commercial C‐peptide assay for use in dogs was available until recently. This assay (Linco Research) has been shown to be effective for measuring pancreatic β‐cell function in diabetic dogs and in dogs with endogenous insulin hypersecretion (Boyd and others 2004).…”
mentioning
confidence: 99%
“…The result clearly stated, that the plasma C-peptide concentration measured during glucagon stimuli, permitted to differentiate between healthy dogs, dogs with diabetes mellitus, and dogs with increased b-cells response to the glucagon challenge, as it would occur with insulin resistance. The C-peptide concentrations during glucagon challenge were heterogenic in diabetic dogs, offering to differentiate between dogs with IDDM and NIDDM or, more precisely put, the severity of b-cell loss in dogs with type-I diabetes (Besch et al 1985, Montgomery et al 1996. Tóth et al (2010) employed human double antibody radioimmunoassay (RIA) for the detection of C-peptide in equine serum with the objective to read C-peptide concentrations, and to be able to analyze pancreatic function based on different stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, a number of studies have shown great success in employing C-peptide as a diagnostic tool (Besch et al 1985, Montgomery et al 1996, Tóth et al 2010, Greco 2016. Not just for the diabetes disease, but as a novel means of non-invasive monitoring of nutritional feed intake, as well as its use in certain therapeutical applications.…”
Section: Introductionmentioning
confidence: 99%